ТHE MODERN STATE OF PROFESSIONAL PREPARATION OF ENGINEERS IS IN TECHNICAL UNIVERSITY - Кокарєва, А. М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
In the article the modern state of professional preparation of engineers is illuminated in a technical university. Key components that affect the improvement of the training effectiveness of future engineers at a technical university are revealed